Impact of Von Willebrand Factor on Bacterial Pathogenesis - Steinert, Michael; Ramming, Isabell; Bergmann, Simone (Frontiers in Medicine, 2020)
Von Willebrand factor (VWF) is a mechano-sensitive protein with crucial functions in normal hemostasis, which are strongly dependant on the shear-stress mediated defolding and multimerization of VWF in the blood stream. Apart from bleeding disorders, higher plasma levels of VWF are often associated with a higher risk of cardiovascular diseases. Herein, the disease symptoms are attributed to the inflammatory response of the activated endothelium and share high similarities to the reaction of the host vasculature to systemic infections caused by pathogenic bacteria such as Staphylococcus aureus and Streptococcus pneumoniae. The bacteria recruit circulating VWF, and by binding to immobilized VWF on activated endothelial cells in blood flow, they interfere with the physiological functions of VWF, including platelet recruitment and coagulation. Several bacterial VWF binding proteins have been identified and further characterized by biochemical analyses. Moreover, the development of a combination of sophisticated cell culture systems simulating shear stress levels of the blood flow with microscopic visualization also provided valuable insights into the interaction mechanism between bacteria and VWF-strings. In vivo studies using mouse models of bacterial infection and zebrafish larvae provided evidence that the interaction between bacteria and VWF promotes bacterial attachment, coagulation, and thrombus formation, and thereby contributes to the pathophysiology of severe infectious diseases such as infective endocarditis and bacterial sepsis. This mini-review summarizes the current knowledge of the interaction between bacteria and the mechano-responsive VWF, and corresponding pathophysiological disease symptoms.